Komunikasi Lingkungan Pada Tradisi Lubuk Larangan Berbasis Ekowisata Di Desa Gema Kabupaten Kampar - Zein, Khairani; Firdaus, Muhammad; Yasir, Yasir (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
Gema Village, Kampar Regency, has a unique river culture. In the river, an area called Lubuk Larangan has tourism potential that is developed based on local wisdom. However, there are several problems found in the lack of proper facilities and infrastructure to support ecotourism activities, lack of promotion and tourism marketing from the local government due to the absence of funding sources for the development of these tours. An effective environmental communication strategy is needed to convey conservation messages to visitors and local communities. This study aims to analyze the environmental communication carried out by Pokdarwis in managing the ecotourism-based Lubuk Larangan tradition in Gema Village, Kampar Regency. This research uses a qualitative method with a descriptive approach. By using purposive technique. Data collection techniques through interviews, observation and documentation. Data analysis techniques use data collection, data reduction, presentation and conclusion drawing. The data checking technique used is triangulation. The results showed that environmental communication carried out by the Tourism Awareness Group (Pokdarwis) played an important role in promoting and appreciating the cultural values and local knowledge contained in the Lubuk Larangan tradition through ecotourism with various communication strategies. This research concludes that by strengthening environmental communication strategies, Pokdarwis can be more effective in encouraging the preservation of the lubuk larangan tradition and supporting the development of sustainable tourism in Gema village.